Optical laminate, image display panel, and image display device
Patent Information
- Application Number
- JP2024206314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-16
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-13
AI Technical Summary
【0011】 本発明によれば、低温環境下での表示不良の抑制により適した光学積層体を提供できる。
Smart Images

Figure 2025037962000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate, an image display panel, and an image display device. [Background technology]
[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices), have rapidly become widespread. These various image display devices have a laminated structure of, for example, an image display cell such as a liquid crystal cell or an EL light-emitting element, and an optical laminate including a polarizing plate and an adhesive sheet. The adhesive sheet is mainly used for bonding between films included in the optical laminate, or for bonding between the image display cell and the optical laminate.
[0003] In an image display device, static electricity is generated during its production, for example, when an optical laminate is attached to an image display cell via an adhesive sheet, or during its use, for example, when a user touches the image display device. If the image display device becomes charged by this static electricity, problems such as display defects can occur.
[0004] Patent Documents 1 and 2 disclose a laminate structure including a polarizing film and a conductive layer containing a conductive polymer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-39132 A [Patent Document 2] Special Publication No. 2015-509615 Summary of the Invention [Problem to be solved by the invention]
[0006] According to the studies of the present inventors, there is room for improvement in the optical laminate from the viewpoint of sufficiently preventing display defects in image display devices. Therefore, an object of the present invention is to provide an optical laminate that is more suitable for suppressing display defects. [Means for solving the problem]
[0007] The present inventors have found that display defects in image display devices tend to occur in low-temperature environments, and have completed the present invention based on this finding.
[0008] The present invention relates to An optical laminate comprising an adhesive sheet, an antistatic layer, and an optical film, the pressure-sensitive adhesive sheet is formed from a pressure-sensitive adhesive composition containing a polymer (A) and an antistatic agent, The surface resistivity of the pressure-sensitive adhesive sheet side of the optical laminate at −15° C. is 1.0×10 10 The present invention provides an optical laminate having a resistivity of Ω / □ or less.
[0009] Further, the present invention relates to There is provided an image display panel including the above optical laminate.
[0010] Further, the present invention relates to The present invention provides an image display device including the above image display panel. Effect of the Invention
[0011] According to the present invention, it is possible to provide an optical laminate that is more suitable for suppressing display defects in a low-temperature environment. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an example of an optical laminate according to this embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates another example of the optical laminate according to this embodiment. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates an example of an image display panel according to the present embodiment. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a schematic diagram of another example of the image display panel according to the present embodiment. [Diagram 5] FIG. 5 is a cross-sectional view that illustrates a schematic diagram of another example of the image display panel according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The optical laminate according to the first aspect of the present invention is An optical laminate comprising an adhesive sheet, an antistatic layer, and an optical film, the pressure-sensitive adhesive sheet is formed from a pressure-sensitive adhesive composition containing a polymer (A) and an antistatic agent, The surface resistivity of the pressure-sensitive adhesive sheet side of the optical laminate at −15° C. is 1.0×10 10 It is less than Ω / □.
[0014] In the second aspect of the present invention, for example, in the optical laminate according to the first aspect, the surface resistivity of the antistatic layer at 25° C. is 3.0×10 8 It is less than Ω / □.
[0015] In a third aspect of the present invention, for example, in the optical laminate according to the first or second aspect, the surface resistivity of the antistatic layer at 25° C. is 1.0×10 7 Ω / □ or more 1.0×10 8 It is less than Ω / □.
[0016] In a fourth aspect of the present invention, for example, in the optical laminate according to any one of the first to third aspects, the polymer (A) is a (meth)acrylic polymer.
[0017] In a fifth aspect of the present invention, for example, in the optical layered body according to any one of the first to fourth aspects, the polymer (A) has a polyether structure.
[0018] In a sixth aspect of the present invention, for example, in the optical layered body according to any one of the first to fifth aspects, the polymer (A) has a constitutional unit derived from a monomer represented by the following formula (1).
[0019] [ka]
[0020] In the formula (1), R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group which may be linear or branched, and n is an integer of 1-15.
[0021] In a seventh aspect of the present invention, for example, an optical laminate according to any one of the first to sixth aspects In the above, the polymer (A) has a structural unit derived from an aromatic ring-containing monomer.
[0022] In an eighth aspect of the present invention, for example, in the optical laminate according to any one of the first to seventh aspects, the pressure-sensitive adhesive composition contains less than 10 parts by weight of the antistatic agent per 100 parts by weight of the polymer (A).
[0023] In a ninth aspect of the present invention, for example, in the optical layered body according to any one of the first to eighth aspects, the glass transition temperature of the polymer (A) calculated from the FOX formula is −40° C. or lower.
[0024] In a tenth aspect of the present invention, for example, in the optical laminate according to the ninth aspect, the glass transition temperature is −45° C. or lower.
[0025] An image display panel according to an eleventh aspect of the present invention comprises: The optical laminate according to any one of the first to tenth aspects is provided.
[0026] An image display device according to a twelfth aspect of the present invention comprises: The image display panel according to the eleventh embodiment is provided.
[0027] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in any manner without departing from the gist of the present invention.
[0028] The optical laminate according to this embodiment includes a pressure-sensitive adhesive sheet, an antistatic layer, and an optical film. The pressure-sensitive adhesive sheet is formed from a pressure-sensitive adhesive composition containing a polymer (A) and an antistatic agent. The surface resistivity of the pressure-sensitive adhesive sheet side of the optical laminate at −15° C. is 1.0×10 10 It is less than Ω / □.
[0029] [Optical laminate] 1 is a cross-sectional view showing a schematic example of an optical laminate according to the present embodiment. The optical laminate 10A includes an adhesive sheet 1, an antistatic layer 2, and an optical film 3. The optical laminate 10A has a structure in which the adhesive sheet 1, the antistatic layer 2, and the optical film 3 are laminated in this order, for example. The optical laminate 10A can be attached to an object (for example, an image display panel) via the adhesive sheet 1.
[0030] The adhesive sheet 1 is formed on the antistatic layer 2. The adhesive sheet 1 and the antistatic layer 2 are laminated together. The adhesive sheet 1 is formed in contact with the antistatic layer 2. The adhesive sheet 1 is formed on one main surface of the antistatic layer 2. In FIG. 1, the adhesive sheet 1 is formed on the entire one main surface of the antistatic layer 2. However, the adhesive sheet 1 may be formed on only a part of one main surface of the antistatic layer 2. In this specification, the "main surface" means the surface of the film or layer having the widest area.
[0031] The antistatic layer 2 is formed on the optical film 3. The antistatic layer 2 and the optical film 3 are laminated together. The antistatic layer 2 is formed in contact with the optical film 3. The antistatic layer 2 is formed on one main surface of the optical film 3. In detail, the optical film 3 is formed on the main surface of the antistatic layer 2 on which the adhesive sheet 1 is not formed. In FIG. 1, the optical film 3 is formed on the entire one main surface of the antistatic layer 2. However, the optical film 3 may be formed on only a part of the one main surface of the antistatic layer 2.
[0032] [Adhesive sheet] The surface resistivity R of the adhesive sheet 1 side of the optical laminate 10A at −15° C. is 1.0×10 10 The optical laminate 10A has a resistivity of 1.0×10 10 By providing the adhesive sheet 1 having a surface resistivity R of Ω / □ or less, display defects due to static electricity in the image display device can be suppressed even in a low temperature environment.
[0033] The surface resistivity R is 5.0 x 10 9 Ω / □ or less, 4.0×10 9 Ω / □ or less, 3.0×10 9 Ω / □ or less, 2.0×10 9 Ω / □ or less, 1.0×10 9 Ω / □ or less, 5.0×10 8 Ω / □ or less, 1.0×10 8 Ω / □ or less, 8.0×10 7 Ω / □ or less, even 6.0×10 7 The lower limit of the surface resistivity R may be, for example, 1.0×10 6 Ω / □, 1.0×10 7 However, when the optical laminate 10A is used in an image display panel having a built-in touch sensing function, the surface resistivity R is preferably 5.0×10 6 Ω / □ or more is preferable, 1.0×10 7More preferably, it is Ω / □ or more. The surface resistivity R can be measured, for example, using a high resistance resistivity meter (for example, Hiresta series manufactured by Mitsubishi Chemical Analytech Co., Ltd.) under conditions of an applied voltage of 250 V and an application time of 10 seconds.
[0034] After the optical laminate 10A was subjected to a weather resistance test, the surface resistivity R′ of the pressure-sensitive adhesive sheet 1 side of the optical laminate 10A at −15° C. was, for example, 1.5×10 10 Ω / □ or less, 1.2×10 10 Ω / □ or less, 1.0×10 10 Ω / □ or less, 9.0×10 9 Ω / □ or less, 8.0×10 9 Ω / □ or less, 7.0×10 9 Ω / □ or less, 6.0×10 9 Ω / □ or less, 5.0×10 9 Ω / □ or less, 1.0×10 9 Ω / □ or less, 5.0×10 8 Ω / □ or less, 1.0×10 8 Ω / □ or less, 8.0×10 7 Ω / □ or less, even 6.0×10 7 The lower limit of the surface resistivity R' may be, for example, 1.0×10 6 Ω / □, 1.0×10 7 The surface resistivity R' may be 5.0×10 8 Ω / □ or less, even 1.0×10 8 When it is Ω / □ or less, display defects can be further suppressed.
[0035] The weather resistance test was carried out in an environment of a temperature of 40° C. and a humidity of 20% RH, in which light with a wavelength of 300 to 700 nm was irradiated from the optical film 3 side of the optical laminate 10A at an illuminance of 500 W / m 2 The weather resistance test can be carried out by continuously irradiating the sample with ultraviolet light for 500 hours. The weather resistance test can be carried out, for example, by using an ultraviolet fade meter (for example, U48HB, manufactured by Suga Test Instruments Co., Ltd.).
[0036] For example, the surface resistivity R' of the adhesive sheet 1 side of the optical laminate 10A at -15°C is unlikely to change before and after the weather resistance test. The ratio R' / R of the surface resistivity R' (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A after the weather resistance test at -15°C to the surface resistivity R (Ω / □) of the adhesive sheet 1 side of the optical laminate 10A before the weather resistance test is, for example, 7.0 or less, and may be 6.0 or less, 5.0 or less, 2.5 or less, 2.0 or less, 1.5 or less, 1.4 or less, 1.3 or less, or even 1.2 or less. The lower limit of the ratio R' / R is, for example, 0.25, 0.5, or even 0.75. When the ratio R' / R is 1.5 or less, display defects can be further suppressed.
[0037] Before the weather resistance test, the surface resistivity R1 of the pressure-sensitive adhesive sheet 1 side of the optical laminate 10A at 25° C. is, for example, 1.0×10 10 The surface resistivity R1 is, for example, 1.0×10 9 Ω / □ or less, 8.0×10 8 Ω / □ or less, 5.0×10 8 Ω / □ or less, 3.0×10 8 Ω / □ or less, 2.0×10 8 Ω / □ or less, 1.0×10 8 Ω / □ or less, 8.0×10 7 Ω / □ or less, 5.0×10 7 Ω / □ or less, even 2.0×10 7 The lower limit of the surface resistivity R1 may be, for example, 1.0×10 6 Ω / □, 1.0×10 7 It may also be Ω / □.
[0038] In the optical laminate 10A, for example, even in a low temperature environment, the surface resistivity of the adhesive sheet 1 side is unlikely to increase. The ratio R / R1 of the surface resistivity R (Ω / □) of the pressure-sensitive adhesive sheet 1 side of the optical laminate 10A at -15°C to the surface resistivity R1 (Ω / □) at -15°C is, for example, 50.0 or less, and may be 40.0 or less, 30.0 or less, 20.0 or less, 15.0 or less, 10.0 or less, 8.0 or less, 7.0 or less, or even 5.0 or less. The lower limit of the ratio R / R1 is, for example, 0.1, and may be 0.5 or even 1.0. When the ratio R / R1 is 50.0 or less, display defects can be further suppressed.
[0039] The ratio R' / R1 of the surface resistivity R'(Ω / □) of the adhesive sheet 1 side of the optical laminate 10A after the weather resistance test at -15°C to the surface resistivity R1(Ω / □) of the adhesive sheet 1 side of the optical laminate 10A before the weather resistance test is, for example, 60.0 or less, 55.0 or less, 50.0 or less, 45.0 or less, 40.0 or less, 35.0 or less, 30.0 or less, 25.0 or less, 20.0 or less, 15.0 or less, 10.0 or less, or even 5.0 or less. The lower limit of the ratio R' / R1 is, for example, 0.25, and may be 0.5, 0.75, or even 1.0. When the ratio R' / R1 is 25.0 or less, 10.0 or less, or even 5.0 or less, display defects can be further suppressed.
[0040] The pressure-sensitive adhesive sheet 1 is formed from a pressure-sensitive adhesive composition (I) containing a polymer (A) and an antistatic agent.
[0041] <Polymer (A)> Examples of the polymer (A) are (meth)acrylic polymers, urethane polymers, silicone polymers, and rubber polymers. The polymer (A) may have a polyether structure. The polymer (A) is preferably a (meth)acrylic polymer. In other words, the pressure-sensitive adhesive composition (I) may contain a (meth)acrylic polymer as a main component. In other words, the pressure-sensitive adhesive composition (I) may be an acrylic pressure-sensitive adhesive composition. The main component means a component having the largest content by weight in the composition. The content of the main component is, for example, 50% by weight or more, and may be 60% by weight or more, 70% by weight or more, 75% by weight or more, or even 80% by weight or more. In this specification, the "(meth)acrylic polymer" means a polymer having a constitutional unit derived from a (meth)acrylic monomer such as (meth)acrylate. The content of the structural unit derived from the (meth)acrylic monomer in the (meth)acrylic polymer is, for example, 40% by weight or more, and may be 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or even 95% by weight or more. The (meth)acrylic polymer may be composed only of structural units derived from the (meth)acrylic monomer. "(Meth)acrylic" means acrylic and methacrylic. "(Meth)acrylate" means acrylate and methacrylate.
[0042] The polymer (A) may have a polyether structure. The polyether structure is a structure containing at least two ether groups (-O-). The polyether structure may be linear or branched. An example of the polyether structure contains an alkyl group, which may be linear or branched, and at least two ether groups. The polymer (A) may have a polyether structure in the main chain or in a side chain, and preferably in the side chain. The polymer (A) may be a (meth)acrylic polymer having a polyether structure in the side chain.
[0043] The polymer (A) may have a structural unit having a polyether structure. In the structural unit, the polyether structure may be located in the main chain or in a side chain, and is preferably located in the side chain. The polymer (A) may have a structural unit derived from a (meth)acrylic monomer having a polyether structure in the side chain.
[0044] The polymer (A) having a polyether structure in the side chain has, for example, a structural unit derived from a monomer (A1) shown in the following formula (1). 1 R in formula (1) is a hydrogen atom or a methyl group. 2 R is an alkyl group which may be linear or branched, and is preferably a linear alkyl group. The number of carbon atoms in the alkyl group may be 1 to 10, or may be 1 to 4. 2 Examples of the R are methyl and ethyl groups. n is an integer of 1 to 15, preferably an integer of 1 to 10, and more preferably an integer of 1 to 5. When n is 1, the monomer (A1) contains two ether groups including the "-O-" of the COO group. The monomer (A1) is a type of (meth)acrylic monomer, and more specifically, a type of (meth)acrylate monomer. The R at the side chain terminal 2 When the O group is taken into consideration, the monomer (A1) is also a type of alkoxy group-containing (meth)acrylate monomer. The structural unit derived from the monomer (A1) has a polyether structure in the side chain.
[0045] [ka]
[0046] Examples of the monomer (A1) are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate, and preferably 2-methoxyethyl acrylate (MEA). The structural unit derived from the monomer (A1) can particularly contribute to a decrease in the surface resistivity of the pressure-sensitive adhesive sheet formed from the pressure-sensitive adhesive composition (I).
[0047] The polymer (A) may have both a structural unit derived from the monomer (A1) and a structural unit derived from the monomer (A2) described below. The polymer (A) having both structural units can contribute to improving the durability of the adhesive strength of the pressure-sensitive adhesive sheet 1.
[0048] The content of the structural unit having a polyether structure in the polymer (A) (e.g., a structural unit derived from the monomer (A1)) may be, for example, 0% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or even 50% by weight or more. The upper limit of the content may be, for example, 100% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, or even less than 60% by weight.
[0049] The polymer (A) may have one or more structural units derived from the following monomer (A2). The monomer (A2) shown below can be copolymerized with the monomer (A1).
[0050] An example of the monomer (A2) is a (meth)acrylic monomer having an alkyl group having 1 to 30 carbon atoms on the side chain. The alkyl group may be linear or branched. Examples of the (meth)acrylic monomer having an alkyl group on the side chain include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and the like.
[0033] Examples of suitable acrylates include but are not limited to, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The content of structural units derived from (meth)acrylic monomers having an alkyl group on the side chain in polymer (A) is, for example, 80% by weight or less, and may be 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, 10% by weight or less, or even 5% by weight or less, or may even be 0% by weight (no such structural units).
[0051] Another example of the monomer (A2) is a hydroxyl group-containing monomer. The hydroxyl group-containing monomer may be a hydroxyl group-containing (meth)acrylic monomer. Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate. From the viewpoint of improving the durability of the pressure-sensitive adhesive sheet formed from the pressure-sensitive adhesive composition (I), 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred, and 4-hydroxybutyl (meth)acrylate is more preferred. The content of the structural unit derived from the hydroxyl group-containing monomer in the polymer (A) is, for example, 1 to 5% by weight, and may be 3% by weight or less, or further 2% by weight or less. The polymer (A) may not have any structural unit derived from the hydroxyl group-containing monomer.
[0052] The monomer (A2) may be an aromatic ring-containing monomer, a carboxyl group-containing monomer, an amino group-containing monomer, or an amide group-containing monomer.
[0053] The aromatic ring-containing monomer may be an aromatic ring-containing (meth)acrylic monomer. Examples of aromatic ring-containing monomers are phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, hydroxyethylated β-naphthol (meth)acrylate, and biphenyl (meth)acrylate. During the manufacture and / or use of an image display device including the optical laminate 10A, the adhesive sheet may be displaced, causing birefringence in the adhesive sheet. This may cause problems such as light leakage and display unevenness in the image display device. By having the polymer (A) have a structural unit derived from an aromatic ring-containing monomer, it is possible to reduce birefringence caused by the adhesive sheet being displaced. This makes it possible to further reduce light leakage and display unevenness in the image display device.
[0054] The aromatic ring-containing monomer may be a structural unit derived from the monomer (A3) shown in the following formula (2). 3 R in formula (2) is a hydrogen atom or a methyl group. 4 is a phenyl group which may be substituted with a hydrogen atom, and is preferably a phenyl group. The substituent of the hydrogen atom is, for example, a linear or branched alkyl group having 1 to 10 or even 1 to 4 carbon atoms, and an alkoxy group having 1 to 4 carbon atoms. n is an integer of 1 to 15, preferably an integer of 1 to 10, and more preferably an integer of 1 to 5. When n is 1, the monomer (A3) contains two ether groups including the "-O-" of the COO group. The monomer (A3) is a type of (meth)acrylic monomer, and more specifically, a type of (meth)acrylate monomer. R at the side chain terminal 4 When the O group is taken into consideration, the monomer (A3) is also a type of alkoxy group-containing (meth)acrylate monomer. It has an ether structure in the side chain.
[0055] [ka]
[0056] An example of a monomer (A3) is phenoxyethyl (meth)acrylate.
[0057] The durability of the optical laminate 10A can be further improved by the polymer (A) having a structural unit derived from the monomer (A3). In addition, the optical laminate 10A tends not to shift at the end even when the optical film 3 shrinks due to heating by the polymer (A) having a structural unit derived from the monomer (A3). Therefore, the optical laminate 10A using the pressure-sensitive adhesive sheet 1 is unlikely to have appearance defects such as light leakage caused by the shrinkage of the optical film 3, even in a high-temperature environment.
[0058] Examples of carboxyl group-containing monomers are (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid. Examples of amino group-containing monomers are N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate. Examples of the amide group-containing monomer include acrylamide-based monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl group-containing lactam-based monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam.
[0059] Monomer (A2) may be a polyfunctional monomer. Examples of polyfunctional monomers are hexanediol di(meth)acrylate (1,6-hexanediol di(meth)acrylate), butanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, epoxy acrylate, polyester acrylate and urethane acrylate; and divinylbenzene. The polyfunctional acrylate is preferably 1,6-hexanediol diacrylate, dipentaerythritol hexa(meth)acrylate.
[0060] The total content of structural units derived from aromatic ring-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, amide group-containing monomers and polyfunctional monomers in polymer (A) is preferably 20% by weight or less, more preferably 15% by weight or less, even more preferably 10% by weight or less, and particularly preferably 8% by weight or less. When polymer (A) has such structural units, the total content is, for example, 0.01% by weight or more, 1% by weight or more. It may be 2% by weight or more, or even 3% by weight or more. The polymer (A) may not have these structural units. In particular, in the polymer (A), the content of the structural units derived from the carboxyl group-containing monomer may be less than 0.1% by weight, or may be 0% by weight (the polymer may not have the structural units).
[0061] Examples of the other monomer (A2) are nitrile group-containing (meth)acrylates such as acrylic acid and (meth)acrylonitrile; epoxy group-containing monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; sulfonic acid group-containing monomers such as sodium vinyl sulfonate; phosphoric acid group-containing monomers; (meth)acrylic acid esters having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyl toluene; olefins or dienes such as ethylene, propylene, butadiene, isoprene and isobutylene; vinyl ethers such as vinyl alkyl ether; and vinyl chloride.
[0062] The total content of the structural units derived from the other monomer (A2) in the polymer (A) is, for example, 30% by weight or less, and may be 10% by weight or less, and is preferably 0% by weight (no such structural units are present).
[0063] The polymer (A) preferably has a glass transition temperature (Tg h ) in the range of -55 ° C. or more, and more preferably has a constitutional unit derived from a (meth)acrylic monomer having a Tg h Preferably, the (meth)acrylic monomer has a constitutional unit having a Tg in the range of -40°C or more. h The (meth)acrylic monomer has a structural unit having a Tg in the range of -30°C or more, and particularly preferably has a Tg h The polymer (A) may have at least one selected from the group consisting of a structural unit derived from a monomer (A3) and a structural unit derived from a (meth)acrylic monomer having an alkyl group having 1 to 3 carbon atoms in the side chain. The Tg hWhen the polymer (A) has a constitutional unit derived from a (meth)acrylic monomer having a temperature in the range of −55° C. or higher, the durability of the optical laminate 10A can be further improved.
[0064] The polymer (A) can be formed by polymerizing one or more of the above-mentioned monomers by a known method. A monomer and a partial polymer of the monomer may be polymerized. The polymerization can be carried out, for example, by solution polymerization, emulsion polymerization, bulk polymerization, thermal polymerization, or active energy ray polymerization. From the viewpoint of forming a pressure-sensitive adhesive sheet having excellent optical transparency, solution polymerization and active energy ray polymerization are preferred. The polymerization is preferably carried out while avoiding contact between the monomer and / or the partial polymer and oxygen, and for this purpose, for example, polymerization in an inert gas atmosphere such as nitrogen or polymerization in a state in which oxygen is blocked by a resin film or the like can be adopted. The polymer (A) to be formed may be any of a random copolymer, a block copolymer, a graft copolymer, and the like.
[0065] The polymerization system for forming the polymer (A) may contain one or more polymerization initiators. The type of polymerization initiator can be selected depending on the polymerization reaction, and may be, for example, a thermal polymerization initiator or a photopolymerization initiator.
[0066] Examples of the solvent used in the solution polymerization include esters such as ethyl acetate and n-butyl acetate, aromatic hydrocarbons such as toluene and benzene, aliphatic hydrocarbons such as n-hexane and n-heptane, alicyclic hydrocarbons such as cyclohexane and methylcyclohexane, and ketones such as methyl ethyl ketone and methyl isobutyl ketone. However, the solvent is not limited to the above examples. The solvent may be a mixture of two or more solvents.
[0067] The polymerization initiator used in the solution polymerization is, for example, an azo-based polymerization initiator, a peroxide-based polymerization initiator, or a redox-based polymerization initiator. The peroxide-based polymerization initiator is, for example, dibenzoyl peroxide or t-butyl permaleate. Among them, the azo-based polymerization initiator disclosed in JP-A-2002-69411 is preferable. The azo-based polymerization initiator is, for example, 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionate) dimethyl, or 4,4'-azobis-4-cyanovaleric acid. However, the polymerization initiator is not limited to the above examples. The amount of the azo-based polymerization initiator used is, for example, 0.05 to 0.5 parts by weight, or may be 0.1 to 0.3 parts by weight, based on 100 parts by weight of the total amount of the monomers.
[0068] The active energy rays used in the active energy ray polymerization are, for example, ionizing radiation such as α rays, β rays, γ rays, neutron rays, and electron beams, and ultraviolet rays. The active energy rays are preferably ultraviolet rays. Polymerization by irradiation with ultraviolet rays is also called photopolymerization. The polymerization system of the active energy ray polymerization typically contains a photopolymerization initiator. The polymerization conditions of the active energy polymerization are not limited as long as the polymer (A) is formed.
[0069] Examples of the photopolymerization initiator include a benzoin ether-based photopolymerization initiator, an acetophenone-based photopolymerization initiator, an α-ketol-based photopolymerization initiator, an aromatic sulfonyl chloride-based photopolymerization initiator, a photoactive oxime-based photopolymerization initiator, a benzoin-based photopolymerization initiator, a benzyl-based photopolymerization initiator, a benzophenone-based photopolymerization initiator, a ketal-based photopolymerization initiator, and a thioxanthone-based photopolymerization initiator, although the photopolymerization initiator is not limited to the above examples.
[0070] Examples of the benzoin ether-based photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethan-1-one, and anisole methyl ether. Examples of the acetophenone-based photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of the α-ketol-based photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of the aromatic sulfonyl chloride-based photopolymerization initiator include 2-naphthalenesulfonyl chloride. An example of the photoactive oxime-based photopolymerization initiator is 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. An example of the benzoin-based photopolymerization initiator is benzoin. An example of the benzyl-based photopolymerization initiator is benzil. An example of the benzophenone-based photopolymerization initiator is benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone. An example of the ketal-based photopolymerization initiator is benzyl dimethyl ketal. An example of the thioxanthone-based photopolymerization initiator is thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0071] The amount of the photopolymerization initiator used is, for example, 0.01 to 1 part by weight, and may be 0.05 to 0.5 parts by weight, relative to 100 parts by weight of the total amount of the monomers.
[0072] The weight average molecular weight (Mw) of the polymer (A) is, for example, 1 million to 3 million, and preferably 1.8 million to 3 million. By making the weight average molecular weight of the polymer (A) 1 million to 3 million, cracks in the pressure-sensitive adhesive sheet can be suppressed, and an increase in viscosity and gelation can be prevented. The weight average molecular weight (Mw) of the polymer in this specification is a value (polystyrene equivalent) based on the measurement by GPC (gel permeation chromatography).
[0073] The content of the polymer (A) in the pressure-sensitive adhesive composition (I) is, for example, 50% by weight or more, and may be 60% by weight or more, 70% by weight or more, 75% by weight or more, or even 80% by weight or more, in terms of solid content ratio. The upper limit of the content is, for example, 99% by weight or less, 97% by weight or less, or even 95% by weight or less.
[0074] <Antistatic agent> The pressure-sensitive adhesive composition (I) contains an antistatic agent. The pressure-sensitive adhesive composition (I) may contain one or more antistatic agents. Examples of the antistatic agent include ionic compounds such as salts. The ionic compound may be an ionic liquid that is liquid at room temperature (25°C).
[0075] Examples of the ionic compound are inorganic cation salts and organic cation salts. Examples of the inorganic cation salts are inorganic cation-anion salts. Examples of the cations contained in the inorganic cation salts are alkali metal ions. Examples of the alkali metal ions are, for example, lithium ions, sodium ions, and potassium ions, and preferably lithium ions. The inorganic cation salt may be a lithium salt.
[0076] An example of an anion contained in an inorganic cation salt is Cl. - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , CH3COO- , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (CN)2N - , C4F9SO3 - , C3F7COO - , (CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - and anions represented by the following general formulas (a) to (d). (a) (C n F 2n+1 SO2)2N - (n is an integer between 1 and 10) (b) CF2(C m F 2m SO2)2N - (m is an integer between 1 and 10) (c) - O3S(CF2) l SO3 - (l is an integer between 1 and 10) (d) (C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (p and q are each independently an integer from 1 to 10)
[0077] The anion contained in the inorganic cation salt is preferably a fluorine-containing anion, more preferably a fluorine-containing imide anion. An example of the fluorine-containing imide anion is an imide anion having a perfluoroalkyl group. A more specific example of the fluorine-containing imide anion is (CF3SO2)(CF3CO)N - or the anion represented by the above general formula (a), (b) or (d), preferably (CF3SO2)2N - , (C2F5SO2)2N -and the like, more preferably (CF3SO2)2N - An example of a preferred inorganic cation salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0078] An example of an organic cation salt is an organic cation-anion salt. An example of a cation contained in an organic cation salt is an organic onium containing an organic group. An example of an onium contained in an organic onium is a nitrogen-containing onium, a sulfur-containing onium, or a phosphorus-containing onium, preferably a nitrogen-containing onium or a sulfur-containing onium. An example of a nitrogen-containing onium is an ammonium cation, a piperidinium cation, a pyrrolidinium cation, a pyridinium cation, a cation having a pyrroline skeleton, a cation having a pyrrole skeleton, an imidazolium cation, a tetrahydropyrimidinium cation, a dihydropyrimidinium cation, a pyrazolium cation, or a pyrazolinium cation. An example of a sulfur-containing onium is a sulfonium cation. An example of a phosphorus-containing onium is a phosphonium cation. An example of an organic group contained in an organic onium is an alkyl group, an alkoxyl group, or an alkenyl group. Specific examples of preferred organic oniums include tetraalkylammonium cations (e.g., tributylmethylammonium cation), alkylpiperidinium cations, and alkylpyrrolidinium cations.
[0079] Examples of the anion contained in the organic cation salt are the same as the examples of the anion contained in the inorganic cation salt. Examples of preferred organic cation salts are 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) and trimethylbutylammonium bis(trifluoromethanesulfonyl)imide.
[0080] The antistatic agent may be a combination of an inorganic cationic salt and an organic cationic salt, and preferably contains an organic cationic salt.
[0081] The amount of the antistatic agent in the pressure-sensitive adhesive composition (I) is, for example, 0.5 parts by weight or more, and may be 1 part by weight or more, 2 parts by weight or more, 3 parts by weight or more, or even 4 parts by weight or more, relative to 100 parts by weight of the polymer (A). The upper limit of the amount is, for example, less than 10 parts by weight, and may be 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, or even 6 parts by weight or less, relative to 100 parts by weight of the polymer (A). By appropriately adjusting the amount of the antistatic agent in the pressure-sensitive adhesive composition (I), the durability of the pressure-sensitive adhesive sheet 1 can be further improved.
[0082] <Radical scavenger> The pressure-sensitive adhesive composition (I) may further contain a radical scavenger. Examples of the radical scavenger include various antioxidants such as hindered phenols, hindered amines, phosphites, phenols, thioethers, and blends of these antioxidants.
[0083] Types of antioxidants are, for example, radical chain inhibitors and peroxide decomposers.
[0084] The antioxidant may be at least one selected from hindered phenol-based, hindered amine-based, and phosphite-based antioxidants.
[0085] The hindered phenol-based antioxidant may have a structure in which a tertiary butyl group is bonded to at least one carbon atom adjacent to a carbon atom on an aromatic ring to which a phenol OH group is bonded. Examples of the hindered phenol antioxidant are dibutylhydroxytoluene (BHT); and Irganox1010, Irganox1010FF, Irganox1035, Irganox1035FF, Irganox1076, Irganox1076FD, Irganox1076DWJ, Irganox1098, Irganox1135, Irganox1330, Irganox1726, Irganox1425WL, Irganox1520L, Irganox245, Irganox245FF, Irganox259, Irganox3114, Irganox565 and Irganox295 (all of which are trade names manufactured by BASF).
[0086] The hindered amine antioxidant may have at least one hindered piperidine group in one molecule. Examples of the hindered amine antioxidant include Adeka STAB LA-63, Adeka STAB LA-63P, Adeka STAB LA-52, and Adeka STAB LA-57 (all of which are trade names, manufactured by ADEKA Corporation).
[0087] Examples of the phosphite antioxidants are triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite; and Adeka STAB 2112, Adeka STAB 2112RG, Adeka STAB 1178, and Adeka STAB 3010 (all of which are trade names, manufactured by ADEKA Corporation).
[0088] Examples of the phenolic antioxidants include monophenolic antioxidants, bisphenolic antioxidants, and polymeric phenolic antioxidants. Examples of the monophenolic antioxidants include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, and stearin-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate. Examples of the bisphenol antioxidant are 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), and 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane. Examples of polymeric phenolic antioxidants are 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione and tocopherol.
[0089] Examples of the thioether-based antioxidant are Adeka STAB AO-503 and Adeka STAB AO-26 (both are trade names, manufactured by ADEKA Corporation).
[0090] The molecular weight of the radical scavenger (e.g., antioxidant) may be 1000 or less, 900 or less, 850 or less, 800 or less, 700 or less, 600 or less, 500 or less, 450 or less, or even 400 or less. The lower limit of the molecular weight is, for example, 100 or more. According to the studies of the present inventors, a radical scavenger having a molecular weight within the above range is particularly suitable for suppressing the amount of radicals generated in a pressure-sensitive adhesive sheet formed from the pressure-sensitive adhesive composition (I).
[0091] The radical scavenger (eg, antioxidant) may be a liquid at 25°C.
[0092] The amount of the radical scavenger in the pressure-sensitive adhesive composition (I) may be, for example, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, or even 0.5 parts by weight or more, relative to 100 parts by weight of the polymer (A). The upper limit of the amount may be, for example, 15 parts by weight or less, 10 parts by weight or less, 7 parts by weight or less, 5 parts by weight or less, less than 5 parts by weight, 4 parts by weight or less, 3 parts by weight or less, or even 2 parts by weight or less, relative to 100 parts by weight of the polymer (A).
[0093] <Additives> The adhesive composition (I) may further contain materials other than the polymer (A), the antistatic agent, and the radical scavenger. Examples of such materials are additives. Examples of additives include crosslinkers, silane coupling agents, colorants such as pigments and dyes, ultraviolet absorbers, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, rework improvers, softeners, polymerization inhibitors, rust inhibitors, inorganic fillers, organic fillers, powders such as metal powders, particles, and foil-like materials. The additives can be blended in a total amount of, for example, 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, per 100 parts by weight of the polymer (A).
[0094] Examples of the crosslinking agent include an organic crosslinking agent and a polyfunctional metal chelate. Examples of the organic crosslinking agent include an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, and an imine crosslinking agent. The organic crosslinking agent and the polyfunctional metal chelate may be of a solvent type or an active energy ray curing type. It can be used for any type of adhesive composition (I). When the adhesive composition (I) is a solvent type, the crosslinking agent is preferably a peroxide-based crosslinking agent or an isocyanate-based crosslinking agent. A peroxide-based crosslinking agent and an isocyanate-based crosslinking agent may be used in combination. The adhesive composition (I) may contain an isocyanate-based crosslinking agent, may contain a peroxide-based crosslinking agent, or may contain both an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent.
[0095] Examples of the isocyanate crosslinking agent include aromatic isocyanate compounds such as tolylene diisocyanate, chlorophenylene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, and polymethylene polyphenyl isocyanate; alicyclic isocyanate compounds such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, hydrogenated diphenylmethane diisocyanate, and isophorone diisocyanate; and aliphatic isocyanate compounds such as butylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate. The isocyanate crosslinking agent may be a compound (adduct) obtained by adding the above isocyanate compound to a polyhydric alcohol compound such as trimethylolpropane; a compound obtained by adding the above isocyanate compound to a polyol such as polyether polyol, polyester polyol, acrylic polyol, polybutadiene polyol, and polyisoprene polyol; or a derivative of the above isocyanate compound such as an isocyanurate. Specific examples of derivatives include trimethylolpropane / tolylene diisocyanate trimer adducts (e.g., Coronate L, manufactured by Tosoh Corporation), trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., Coronate HL, manufactured by Tosoh Corporation), and isocyanurates of hexamethylene diisocyanate (e.g., Coronate HX, manufactured by Tosoh Corporation).
[0096] When the pressure-sensitive adhesive composition (I) contains an isocyanate-based crosslinking agent, the amount thereof is, for example, 0.1 to 10 parts by weight, and may be 0.2 to 5 parts by weight, 0.25 to 3 parts by weight, 0.3 to 1 part by weight, or even 0.3 to 0.5 parts by weight, relative to 100 parts by weight of the polymer (A).
[0097] Examples of peroxide crosslinking agents include di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, benzoyl peroxide, t-butylperoxyisobutyrate, and 1,1-di(t-hexylperoxy)cyclohexane. The peroxide crosslinking agent may be benzoyl peroxide because of its excellent crosslinking reaction efficiency.
[0098] When the pressure-sensitive adhesive composition (I) contains a peroxide-based crosslinking agent, the amount thereof is, for example, 0.005 to 5 parts by weight, and may be 0.01 to 3 parts by weight, 0.05 to 2 parts by weight, 0.07 to 1 part by weight, 0.07 to 0.5 parts by weight, 0.07 to 0.3 parts by weight, or even 0.07 to 0.2 parts by weight, relative to 100 parts by weight of the polymer (A).
[0099] Examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane;
[0100] When the pressure-sensitive adhesive composition (I) contains a silane coupling agent, the blending amount thereof is, for example, 5 parts by weight or less, and may be 3 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.2 parts by weight or less, 0.1 parts by weight or less, or even 0.05 parts by weight or less, based on 100 parts by weight of the polymer (A). The pressure-sensitive adhesive composition (I) does not need to contain a silane coupling agent.
[0101] The type of the pressure-sensitive adhesive composition (I) is, for example, an emulsion type, a solvent type (solution type), an active energy ray curing type (photocuring type), or a hot melt type (hot melt type). From the viewpoint of forming a pressure-sensitive adhesive sheet having excellent durability, the pressure-sensitive adhesive composition (I) may be a solvent type or an active energy ray curing type, or may be a solvent type. The solvent-type pressure-sensitive adhesive composition (I) may not contain a photocuring agent such as an ultraviolet curing agent.
[0102] The pressure-sensitive adhesive composition (I) can be used, for example, in an optical laminate. In other words, the pressure-sensitive adhesive composition (I) may be for an optical laminate. However, the use of the pressure-sensitive adhesive composition (I) is not limited to the above examples.
[0103] In this embodiment, when the polymer (A) is synthesized from the above monomer group, the glass transition temperature Tg of the polymer (A) calculated from the FOX formula may be -40°C or lower. The glass transition temperature Tg of the polymer (A) tends to correlate with the glass transition temperature of the adhesive sheet 1. When the glass transition temperature Tg of the polymer (A) is, for example, -40°C or lower, the polymer (A) contained in the adhesive sheet is unlikely to have a small free volume even in a low temperature environment. When the free volume of the polymer (A) is unlikely to be small, a space in which the antistatic agent can move is likely to be generated in the adhesive sheet 1. This makes it easier for the antistatic agent to move within the adhesive sheet 1, and the increase in the surface resistivity can be further suppressed. In addition, when the glass transition temperature Tg of the polymer (A) is, for example, -40°C or lower, the optical laminate 10A can further suppress the increase in the surface resistivity on the adhesive sheet 1 side, for example, even in a low temperature environment. That is, the ratio R / R1 can be made smaller.
[0104] The glass transition temperature Tg is, for example, −40° C. or lower, −44° C. or lower, further −45° C. or lower, and may be −50° C. or lower. The lower limit of the glass transition temperature Tg is, for example, −70° C., and may be −60° C. The formula of FOX is expressed by the following formula. 1 / Tg=w1 / Tg1+w2 / Tg2+···+w m / Tg m
[0105] In the above formula, Tg is the glass transition temperature [K] of the polymer (A). w1, w2, ... w m are the weight fractions of each monomer in the monomer group. Tg1, Tg2, ...Tg m and Tg1 are the glass transition temperatures [K] of the single polymer of each monomer. m is a positive integer. As an example, w1 is the weight fraction of the first monomer in the monomer group, and Tg1 is the glass transition temperature [K] of the single polymer of the first monomer. The glass transition temperature [K] of polymer (A) is calculated from the above formula, and the glass transition temperature Tg [°C] of polymer (A) can be calculated by converting the unit.
[0106] [Anti-static layer] The antistatic layer 2 is a layer containing a conductive material. The conductive material may be a material other than ITO, such as a conductive polymer, a complex of a conductive polymer and a dopant, an ionic surfactant, conductive fine particles, an ionic compound, etc.
[0107] Examples of the conductive polymer include polythiophene, polyaniline, polypyrrole, polyquinoxaline, polyacetylene, polyphenylenevinylene, polynaphthalene, and the like. and derivatives thereof. The conductive material may contain one or more of these conductive polymers. As the conductive polymer, polythiophene, polyaniline and derivatives thereof are preferred, and polythiophene derivatives are particularly preferred. Polythiophene, polyaniline and derivatives thereof function as, for example, conductive polymers having water solubility or water dispersibility. When the conductive polymer is water soluble or water dispersible, the antistatic layer 2 can be prepared using an aqueous solution or aqueous dispersion of the conductive polymer. In this case, since it is not necessary to use a non-aqueous organic solvent to prepare the antistatic layer 2, deterioration of the optical film 3 and the like due to the organic solvent can be suppressed.
[0108] The conductive polymer may have a hydrophilic functional group. Examples of the hydrophilic functional group include a sulfone group, an amino group, an amide group, an imino group, a hydroxyl group, a mercapto group, a hydrazino group, a carboxyl group, a sulfate group, a phosphate group, and salts thereof (e.g., quaternary ammonium bases). When the conductive polymer has a hydrophilic functional group, the conductive polymer tends to be easily dissolved in water, or the fine particle-shaped conductive polymer tends to be easily dispersed in water.
[0109] From the viewpoint of electrical conductivity and chemical stability, the conductive polymer is preferably poly(3,4-disubstituted thiophene). Examples of poly(3,4-disubstituted thiophene) include poly(3,4-alkylenedioxythiophene) and poly(3,4-dialkoxythiophene), and poly(3,4-alkylenedioxythiophene) is preferable. Poly(3,4-alkylenedioxythiophene) has a structural unit represented by the following formula (I), for example.
[0110] [ka]
[0111] In formula (I), R 1is, for example, an alkylene group having 1 to 4 carbon atoms. The alkylene group may be linear or branched. Examples of the alkylene group include a methylene group, a 1,2-ethylene group, a 1,3-propylene group, a 1,4-butylene group, a 1-methyl-1,2-ethylene group, a 1-ethyl-1,2-ethylene group, a 1-methyl-1,3-propylene group, and a 2-methyl-1,3-propylene group, and preferably a methylene group, a 1,2-ethylene group, or a 1,3-propylene group, and more preferably a 1,2-ethylene group. The conductive polymer is preferably poly(3,4-ethylenedioxythiophene) (PEDOT).
[0112] The dopant may be, for example, a polyanion. When the conductive polymer is polythiophene (or a derivative thereof), the polyanion forms an ion pair with the polythiophene (or a derivative thereof), and the polythiophene (or a derivative thereof) can be stably dispersed in water. The polyanion is not particularly limited, and may be, for example, carboxylic acid polymers such as polyacrylic acid, polymaleic acid, and polymethacrylic acid; sulfonic acid polymers such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid; and the like. The polyanion may be a copolymer of vinyl carboxylic acids or vinyl sulfonic acids with other monomers. The other monomers may be, for example, (meth)acrylated polymers. Examples of the polyanion include aromatic vinyl compounds such as styrene and vinylnaphthalene. The polyanion is particularly preferably polystyrene sulfonic acid (PSS). Examples of the composite of a conductive polymer and a dopant include a composite of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS).
[0113] Examples of ionic surfactants include cationic surfactants such as quaternary ammonium salt type, phosphonium salt type, and sulfonium salt type; anionic surfactants such as carboxylic acid type, sulfonate type, sulfate type, phosphate type, and phosphite type; amphoteric surfactants such as sulfobetaine type, alkylbetaine type, and alkylimidazolium betaine type; and nonionic surfactants such as polyhydric alcohol derivatives, β-cyclodextrin inclusion compounds, sorbitan fatty acid monoesters, sorbitan fatty acid diesters, polyalkylene oxide derivatives, and amine oxides.
[0114] Examples of the conductive fine particles include metal oxide fine particles such as tin oxide, antimony oxide, indium oxide, and zinc oxide, and tin oxide fine particles are preferred. Examples of materials for tin oxide fine particles include tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, titanium oxide-cerium oxide-tin oxide complex, and titanium oxide-tin oxide complex. The average particle diameter of the conductive fine particles is, for example, 1 to 100 nm, and preferably 2 to 50 nm. The average particle diameter of the conductive fine particles means a particle diameter (d50) corresponding to 50% cumulative volume in a particle size distribution measured by, for example, a laser diffraction particle sizer.
[0115] As the ionic compound, for example, the ionic compounds explained above in the <Antistatic agent> can be used.
[0116] Other examples of conductive materials include carbon materials such as acetylene black, ketjen black, natural graphite, artificial graphite, and carbon nanotubes (CNTs); titanium black; homopolymers of monomers having a cationic conductive group such as a quaternary ammonium salt, an amphoteric ionic conductive group such as a betaine compound, an anionic conductive group such as a sulfonate, or a nonionic conductive group such as glycerin, or copolymers of such monomers with other monomers (for example, polymers having ionic conductivity such as polymers having structural units derived from acrylate or methacrylate having a quaternary ammonium base); and alloys of hydrophilic polymers such as copolymers of ethylene and methacrylate with acrylic resins or the like (permanent antistatic agents).
[0117] From the viewpoints of transparency, total light transmittance, appearance, antistatic effect, and stability of the antistatic effect under high temperature or high humidity environment, the antistatic layer 2 preferably contains at least one selected from the group consisting of conductive polymers and carbon materials, and more preferably contains a carbon material. Carbon materials are not easily decomposed under high temperature and high humidity environment and / or ultraviolet light irradiation. Therefore, by containing a carbon material in the antistatic layer 2, weather resistance can be improved. In addition, by containing a carbon material in the antistatic layer 2, the optical laminate 10A can further suppress an increase in the surface resistivity on the adhesive sheet 1 side, for example, even under a low temperature environment. That is, the ratio R / R1 can be made smaller.
[0118] The antistatic layer 2 may further contain other materials such as a binder in addition to the conductive material. The binder tends to improve the film-forming properties of the conductive material, and also to improve the adhesion and bonding strength (anchoring power) of the antistatic layer 2 to the optical film 3. Examples of the binder include oxazoline group-containing polymers, polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, epoxy resins, polyvinylpyrrolidone, polystyrene resins, polyethylene resins, and the like. Examples of binders include ethylene glycol and pentaerythritol, and preferably, oxazoline group-containing polymers, polyurethane resins, polyester resins, and acrylic resins, and more preferably, polyurethane resins. The antistatic layer 2 may contain one or more of these binders. The content of the binder in the antistatic layer 2 is, for example, 1% by weight to 90% by weight, and preferably 10% by weight to 80% by weight.
[0119] In the optical laminate 10A, the surface resistivity of the antistatic layer 2 at 25° C. is, for example, 3.0×10 8 The surface resistivity of the antistatic layer 2 at 25° C. is, for example, 3.0×10 8 By being Ω / □ or less, display defects due to charging of a liquid crystal display device including the optical laminate 10A can be more effectively prevented even in an environment where static electricity is likely to be generated. The surface resistivity of the antistatic layer 2 can be specified by the following method. First, a laminate in which the surface of the antistatic layer 2 is exposed to the outside is prepared. An example of such a laminate is a laminate L1 consisting of an optical film 3 and an antistatic layer 2. Next, the surface resistivity of the surface of the antistatic layer 2 in the prepared laminate is measured. The surface resistivity of the antistatic layer 2 can be measured using a Hiresta MCP-HT800 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with the method specified in JIS K6911:1995.
[0120] The surface resistivity of the antistatic layer 2 is preferably 2.0×10 8 Ω / □ or less, and more preferably 1.0×10 8 Ω / □, and more preferably less than 7.0×10 7 Ω / □ or less, and particularly preferably 5.0×10 7 The lower limit of the surface resistivity of the antistatic layer 2 is, for example, 1.0×10 2 Ω / □, and 1.0×10 5 Ω / □, especially 1.0×10 7When the optical laminate 10A is used in a liquid crystal display device equipped with a touch sensor or a touch panel, the surface resistivity of the antistatic layer 2 is set to 1.0×10 in order to ensure sufficient sensitivity of the touch sensor or the touch panel provided in the liquid crystal display device. 7 It may be larger than Ω / □.
[0121] The thickness of the antistatic layer 2 is, for example, 5 nm to 180 nm, preferably 150 nm or less, more preferably 140 nm or less, and in some cases 100 nm or less. The thickness of the antistatic layer 2 may be 10 nm or more, 20 nm or more, 50 nm or more, or even 55 nm or more, and may be 70 nm or more to suppress an increase in the surface resistivity in the low temperature range, and may be 100 nm or more in some cases. By appropriately adjusting the thickness of the antistatic layer 2, the antistatic effect can be further improved. In addition, by appropriately adjusting the thickness of the antistatic layer 2, the value of the ratio R / R1 in the optical laminate 10A can be further reduced.
[0122] [Optical film] The optical film 3 includes, for example, at least one selected from the group consisting of a polarizing film and a retardation film. The optical film 3 may be a laminated film including a polarizing film and / or a retardation film. The optical film 3 may include a glass film.
[0123] The polarizing film includes a polarizer. The polarizing film typically includes a polarizer and a protective film (transparent protective film). The protective film is disposed, for example, in contact with the main surface of the polarizer. The polarizer may be disposed between two protective films. The protective film may be disposed on at least one surface of the polarizer.
[0124] The polarizer is not particularly limited, and examples thereof include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing dichroic substances such as iodine and dichroic dyes; dehydrated polyvinyl alcohol; and dehydrochlorinated polyvinyl chloride. Examples of the polarizer include polyene-based oriented films such as those made of polyvinyl alcohol-based films (polyvinyl alcohol-based films include partially saponified ethylene-vinyl acetate copolymer films) and dichroic substances such as iodine.
[0125] The thickness of the polarizer is not particularly limited, and may be, for example, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or even 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, and may be, for example, 1 μm or more, 5 μm or more, 10 μm or more, or even 15 μm or more. A thin polarizer (for example, a thickness of 20 μm or less) is suppressed in dimensional change, and can contribute to improving the durability of the optical laminate, particularly the durability at high temperatures.
[0126] As the material of the protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film may be a thermosetting resin or an ultraviolet-curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone-based resin. When the polarizing film has two protective films, the materials of the two protective films may be the same or different from each other. For example, a protective film made of a thermoplastic resin may be bonded to one main surface of the polarizer via an adhesive, and a protective film made of a thermosetting resin or an ultraviolet-curing resin may be bonded to the other main surface of the polarizer. The protective film may contain one or more types of optional additives, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, color inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0127] The thickness of the protective film can be appropriately determined, but is generally about 10 to 200 μm in terms of strength, workability such as handleability, thinness, and the like.
[0128] The polarizer and the protective film are usually adhered to each other via a water-based adhesive or the like. Examples of the water-based adhesive include an isocyanate-based adhesive, a polyvinyl alcohol-based adhesive, a gelatin-based adhesive, a vinyl-based latex, a water-based polyurethane, and a water-based polyester. Examples of adhesives other than the above-mentioned adhesives include an ultraviolet-curable adhesive and an electron beam-curable adhesive. The electron beam-curable polarizing plate adhesive exhibits suitable adhesion to various protective films. The adhesive may contain a metal compound filler.
[0129] In the polarizing film, a retardation film or the like can be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like can be further provided on the protective film.
[0130] The protective film may have a hard coat layer on the surface opposite to the surface bonded to the polarizer, and may also be subjected to treatments for the purposes of anti-reflection, anti-sticking, diffusion, anti-glare, etc.
[0131] The polarizing film may be a circular polarizing film.
[0132] The retardation film may be one obtained by stretching a polymer film or one obtained by aligning and fixing a liquid crystal material. The retardation film has birefringence, for example, in the in-plane and / or thickness direction.
[0133] Examples of retardation films include anti-reflection retardation films (see JP 2012-133303 A,
[0221] ,
[0222] ,
[0228] ), viewing angle compensation retardation films (see JP 2012-133303 A,
[0225] ,
[0226] ), and tilted orientation retardation films for viewing angle compensation (see JP 2012-133303 A,
[0227] ).
[0134] As the retardation film, as long as it substantially has the above-mentioned functions, for example, the retardation value, arrangement angle, three-dimensional birefringence, whether it is a single layer or a multilayer, and the like are not particularly limited, and a known retardation film can be used.
[0135] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm.
[0136] The retardation film is composed of, for example, two layers, a quarter-wave plate and a half-wave plate, in which liquid crystal material is oriented and fixed.
[0137] [Method of manufacturing optical laminate] The optical laminate 10A includes, for example, producing a laminate L2 consisting of a substrate and an adhesive sheet 1, producing a laminate L1 consisting of an optical film 3 and an antistatic layer 2, and transferring the adhesive sheet 1 of the laminate L2 onto the antistatic layer 2 of the laminate L1.
[0138] (Method of manufacturing laminate L1) First, a solution or dispersion of the conductive material is prepared. The solvent of the solution or dispersion is, for example, water, and may further contain a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-amyl alcohol, isoamyl alcohol, sec-amyl alcohol, tert-amyl alcohol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, and cyclohexanol.
[0139] Next, a solution or dispersion of a conductive material is applied to the surface of the optical film 3. The resulting coating film is dried to form the antistatic layer 2 on the optical film 3. In this way, a laminate L1 consisting of the optical film 3 and the antistatic layer 2 is obtained.
[0140] (Method of manufacturing laminate L2) The pressure-sensitive adhesive sheet 1 is formed from a pressure-sensitive adhesive composition (I). The pressure-sensitive adhesive sheet 1 contains, for example, a crosslinked product of a (meth)acrylic polymer. The pressure-sensitive adhesive sheet 1 is formed from the pressure-sensitive adhesive composition (I) by the following method.
[0141] The method for producing the pressure-sensitive adhesive sheet 1 includes, for example, applying the pressure-sensitive adhesive composition (I) to a substrate to form a coating film, and drying the resulting coating film. The coating film is dried to form the pressure-sensitive adhesive sheet 1 on the substrate. This results in a laminate L2 consisting of the substrate and the pressure-sensitive adhesive sheet 1.
[0142] The substrate may be, for example, a release film. The adhesive sheet 1 formed on the release film may be transferred to, for example, an optical film. The substrate may be an optical film.
[0143] The release film can be used as a release liner after the adhesive sheet 1 is transferred to the antistatic layer 2 until the adhesive sheet 1 is put to practical use, thus simplifying the process. can.
[0144] Examples of materials constituting the release film include suitable thin sheets such as porous materials such as plastic films, paper, cloth, and nonwoven fabrics, nets, foam sheets, metal foils, and laminates thereof, among which plastic films are preferably used because of their excellent surface smoothness.
[0145] The plastic film is not particularly limited, and examples thereof include a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polybutylene terephthalate film, a polyurethane film, and an ethylene-vinyl acetate copolymer film.
[0146] The thickness of the release film is usually 5 to 200 μm, and preferably about 5 to 100 μm. The release film is subjected to a release treatment such as a silicone-based, fluorine-based, or long-chain alkyl-based treatment. The release film may be subjected to a release and antifouling treatment using a fatty acid amide-based release agent, silica powder, or the like, or an antistatic treatment such as a coating type, kneading type, or deposition type.
[0147] A solution (adhesive solution) containing the adhesive composition (I) may be applied to the substrate. The solid content of the adhesive solution is, for example, 5 to 50% by weight, and preferably 10 to 40% by weight. The adhesive solution can be prepared by appropriately adding the same solvent as the polymerization solvent or a different solvent to the adhesive composition (I) depending on the polymerization form of the (meth)acrylic polymer (A).
[0148] Various methods are used to apply the pressure-sensitive adhesive composition (I) to the substrate, and examples of such methods include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and extrusion coating using a die coater, etc. The amount of pressure-sensitive adhesive composition (I) to be applied can be appropriately adjusted depending on the desired thickness of the pressure-sensitive adhesive sheet 1.
[0149] The coating film is dried to harden the coating film, forming the adhesive sheet 1. The drying temperature of the coating film is, for example, 130° C. or less, preferably 125° C. or less, more preferably 120° C. or less, even more preferably 110° C. or less, and particularly preferably 100° C. or less. The drying temperature of the coating film may be 60° C. or more, or 80° C. or more. When the drying temperature is 60° C. or more, for example, the reaction of the isocyanate-based crosslinking agent proceeds smoothly, the cohesive force of the adhesive sheet 1 can be improved, and display unevenness of the image display device tends to be reduced. When the drying temperature is 130° C. or less, for example, the reaction speed of the isocyanate-based crosslinking agent can be appropriately adjusted, and transparency tends to be ensured.
[0150] The drying time for the coating film can be appropriately adjusted depending on the composition of the pressure-sensitive adhesive composition (I) and is preferably 30 to 300 seconds, more preferably 40 to 240 seconds, and particularly preferably 60 to 180 seconds.
[0151] The thickness of the adhesive sheet 1 is not particularly limited and may be 2 to 150 μm, 2 to 100 μm, or 5 to 50 μm. By appropriately adjusting the thickness of the adhesive sheet 1, it is possible to improve the adhesion between the adhesive sheet 1 and the antistatic layer 2. In addition, by appropriately adjusting the thickness of the adhesive sheet 1, it is possible to suppress peeling of the adhesive sheet 1 from an adherend such as glass or an image display device.
[0152] The adhesive sheet 1 of the laminate L2 obtained above is transferred onto the antistatic layer 2 of the laminate L1. In this way, an optical laminate 10A consisting of the optical film 3, the antistatic layer 2, and the adhesive sheet 1 is obtained.
[0153] Fig. 2 is a cross-sectional view showing a schematic diagram of another example of the optical laminate according to the present embodiment. As shown in Fig. 2, the optical laminate 10B has a laminated structure in which a release liner 4, a pressure-sensitive adhesive sheet 1, an antistatic layer 2, and an optical film 3 are laminated in this order. After the release liner 4 is peeled off, the optical laminate 10B can be used by, for example, attaching it to an image display cell. The following examples may be combined with each other as long as there is no technical contradiction.
[0154] Examples of materials constituting the release liner 4 include suitable thin sheets, such as plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester film; porous materials such as paper, cloth, and nonwoven fabric; nets, foam sheets, metal foils, and laminates of these; and plastic films are preferably used because of their excellent surface smoothness.
[0155] The plastic film is not particularly limited as long as it is a film capable of protecting the adhesive sheet 1, and examples include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate copolymer film, etc.
[0156] The thickness of the release liner 4 is usually 5 to 200 μm, and preferably about 5 to 100 μm. The release liner 4 may be subjected to a release and antifouling treatment using a silicone-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent, silica powder, or the like, as necessary, or an antistatic treatment such as a coating type, kneading type or deposition type. In particular, by appropriately subjecting the surface of the release liner 4 to a release treatment such as a silicone treatment, a long-chain alkyl treatment or a fluorine treatment, the releasability from the pressure-sensitive adhesive sheet 1 can be further improved.
[0157] As described above, the release film used when producing the pressure sensitive adhesive sheet 1 may be used as the release liner 4.
[0158] The optical laminate of this embodiment can be distributed and stored, for example, as a rolled body obtained by winding a strip-shaped optical laminate, or as a sheet-shaped optical laminate. The optical laminate of this embodiment is suitable for use as an image display device used in an environment where static electricity is particularly likely to occur, particularly an in-vehicle display. Examples of in-vehicle displays include panels for car navigation devices, cluster panels, and mirror displays. A cluster panel is a panel that displays the vehicle's running speed, engine revolutions, and the like.
[0159] [Embodiment of Image Display Panel] Fig. 3 is a cross-sectional view showing an example of an image display panel according to the present embodiment. As shown in Fig. 3, the image display panel 11A includes an optical laminate 10A, and further includes, for example, an image display cell 30A. In detail, the optical laminate 10A is bonded to the image display cell 30A via an adhesive sheet 1.
[0160] The image display cell 30A includes, for example, an image forming layer 32, a first transparent substrate 31, and a second transparent substrate 33. The image forming layer 32 is, for example, disposed between the first transparent substrate 31 and the second transparent substrate 33, and is in contact with each of the first transparent substrate 31 and the second transparent substrate 33. The adhesive sheet 1 of the optical laminate 10A is, for example, disposed between the first transparent substrate 31 of the image display cell 30A and the second transparent substrate 33. It is adjacent to.
[0161] The image forming layer 32 is, for example, a liquid crystal layer containing liquid crystal molecules that are homogeneously aligned in the absence of an electric field. A liquid crystal layer containing such liquid crystal molecules is suitable for an IPS (In-Plane-Switching) mode. However, the liquid crystal layer may be used for a TN (Twisted Nematic) type, an STN (Super Twisted Nematic) type, a π type, a VA (Vertical Alignment) type, or the like. In this specification, an image display cell having a liquid crystal layer may be called a liquid crystal cell, and an image display panel having a liquid crystal cell may be called a liquid crystal panel. The image forming layer 32 may be an EL light-emitting layer.
[0162] The image forming layer 32 has a thickness of, for example, 1.5 μm to 4 μm.
[0163] Examples of materials for the first transparent substrate 31 and the second transparent substrate 33 include glass and polymer. In this specification, a transparent substrate made of a polymer may be referred to as a polymer film. Examples of polymers constituting the transparent substrate include polyethylene terephthalate, polycycloolefin, and polycarbonate. The thickness of the transparent substrate made of glass is, for example, 0.1 mm to 1 mm. The thickness of the transparent substrate made of a polymer is, for example, 10 μm to 200 μm.
[0164] The image display cell 30A may further include layers other than the image forming layer 32, the first transparent substrate 31, and the second transparent substrate 33. Examples of the other layers include a color filter, an easy-adhesion layer, and a hard coat layer. The color filter is, for example, disposed on the viewing side of the image forming layer 32, and is preferably located between the first transparent substrate 31 and the adhesive sheet 1 of the optical laminate 10A. The easy-adhesion layer and the hard coat layer are, for example, disposed on the surface of the first transparent substrate 31 or the second transparent substrate 33.
[0165] The image display panel 11A may further include other members than the optical laminate 10A and the image display cell 30A. For example, the image display panel 11A may further include a conductive structure (not shown) electrically connected to the side of the optical laminate 10A. If the conductive structure is connected to earth, it is easy to prevent the optical laminate 10A from being charged by static electricity. The conductive structure may cover the entire side of the optical laminate 10A, or may cover only a part of the side of the optical laminate 10A. The ratio of the area of the side of the optical laminate 10A covered by the conductive structure to the area of the entire side of the optical laminate 10A is, for example, 1% or more, and preferably 3% or more.
[0166] Examples of materials for the conductive structure include conductive pastes made of metals such as silver and gold, conductive adhesives, and other conductive materials. The conductive structure may be wiring extending from the side surface of the optical laminate 10A.
[0167] The image display panel 11A may further include other optical films in addition to the optical film 3. Examples of the other optical films include films used in image display devices, such as a polarizing plate, a reflecting plate, a transmissive plate, a viewing angle compensation film, and a brightness enhancement film. The image display panel 11A may include one or more of these other optical films.
[0168] When the other optical film is a polarizing plate, the polarizing plate is bonded to the second transparent substrate 33 of the image display cell 30A, for example, via an adhesive sheet. This polarizing plate has, for example, the configuration described above for the optical film 3. In the polarizing plate as the other optical film, the transmission axis (or absorption axis) of the polarizer is, for example, perpendicular to the transmission axis (or absorption axis) of the polarizer in the polarizing plate. As the material of the adhesive sheet for bonding the polarizing plate and the second transparent substrate 33, the materials described above for the adhesive sheet 1 can be used. The adhesive sheet The thickness is not particularly limited and is, for example, 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and further preferably 5 to 35 μm.
[0169] FIG. 4 is a cross-sectional view showing a schematic diagram of another example of the image display panel according to the present embodiment. As shown in FIG. 4, the image display panel 11B further includes a conductive layer 40 disposed between the optical laminate 10A and the image display cell 30A. However, the image display panel is preferably the image display panel 11A that does not include the conductive layer 40. In the image display panel 11B provided with the conductive layer 40, the reflectance tends to be high, and the visibility of the display may be reduced. In the image display panel 11A that does not include the conductive layer 40, it is preferable to provide a conductive portion (the above-mentioned conductive structure) adjacent to the adhesive sheet 1. As the conductive portion, for example, a conductive silver paste is used. After bonding the optical laminate 10A to the image display cell 30A, a conductive portion is provided by applying a conductive silver paste or the like to the side portion of the adhesive sheet 1, and the conductive portion is electrically connected to other wiring or the housing of the image display device, thereby improving the antistatic property of the image display panel.
[0170] The conductive layer 40 is, for example, a layer containing a conductive agent. As the conductive agent, metal oxides, conductive polymers, those described above for the adhesive sheet 1 and the antistatic layer 2, and the like can be used. The thickness of the conductive layer 40 is, for example, 5 nm to 180 nm. The surface resistivity of the conductive layer 40 is, for example, 1.0×10 6 Ω / □~1.0×10 10 Ω / □, preferably 1.0×10 8 Ω / □~1.0×10 9 It is Ω / □.
[0171] The image display panel of the present embodiment may be an image display panel having a built-in touch sensing function. An example of an image display panel having a built-in touch sensing function is shown in FIG. 5. FIG. 5 is a cross-sectional view that shows a schematic diagram of another example of the image display panel according to the present embodiment. As shown in FIG. 5, the image display panel 11C includes an image display cell 30B further including a touch sensing electrode portion 35. In the image display cell 30B, the touch sensing electrode portion 35 is disposed between the first transparent substrate 31 and the second transparent substrate 33. The touch sensing electrode portion 35 has a touch sensor and a touch driving function. The image display panel 11C is a so-called in-cell type image display panel, and the image display cell 30B is a so-called in-cell type image display cell. However, in the image display cell 30B, the touch sensing electrode portion 35 may be disposed on the viewing side of the first transparent substrate 31. That is, the image display panel 11C may be a so-called on-cell type image display panel, and the image display cell 30B may be a so-called on-cell type image display cell.
[0172] The touch sensing electrode unit 35 has, for example, a touch sensor electrode 36 and a touch drive electrode 37. The touch sensor electrode 36 means a (receiving) electrode for touch detection. The touch sensor electrode 36 and the touch drive electrode 37 can be formed independently in various patterns. For example, when the image display cell 30B is flat, the touch sensor electrode 36 and the touch drive electrode 37 can be provided independently in the X-axis direction and the Y-axis direction, respectively, and can be formed in a pattern in which they intersect at right angles. In FIG. 5, in the touch sensing electrode unit 35, the touch sensor electrode 36 is disposed closer to the viewing side than the touch drive electrode 37. However, the touch drive electrode 37 may be disposed closer to the viewing side than the touch sensor electrode 36. In the touch sensing electrode unit 35, the touch sensor electrode 36 and the touch drive electrode 37 may be integrated.
[0173] 5, the touch sensing electrode unit 35 is disposed between the image forming layer 32 and the first transparent substrate 31 (on the viewing side of the image forming layer 32). However, the touch sensing electrode unit 35 may also be disposed between the image forming layer 32 and the second transparent substrate 33 (on the lighting system side of the image forming layer 32).
[0174] In the touch sensing electrode unit 35, the touch sensor electrode 36 and the touch drive electrode 37 may not be in contact with each other. For example, the touch sensor electrode 36 may be disposed between the image forming layer 32 and the first transparent substrate 31, and the touch drive electrode 37 may be disposed between the image forming layer 32 and the second transparent substrate 33.
[0175] The drive electrode in the touch sensing electrode portion 35 (the touch drive electrode 37, or an electrode in which the touch sensor electrode 36 and the touch drive electrode 37 are integrated) can also serve as a common electrode that controls the image formation layer 32.
[0176] The touch sensor electrode 36 (capacitive sensor) and the touch drive electrode 37 constituting the touch sensing electrode unit 35, or an electrode formed by integrating these, function as a transparent conductive layer. The material of this transparent conductive layer is not particularly limited, and examples thereof include metals such as gold, silver, copper, platinum, palladium, aluminum, nickel, chromium, titanium, iron, cobalt, tin, magnesium, and tungsten, and alloys thereof. The material of the transparent conductive layer may be an oxide of a metal such as indium, tin, zinc, gallium, antimony, zirconium, and cadmium. Specific examples of this oxide include indium oxide, tin oxide, titanium oxide, cadmium oxide, and mixtures thereof. The material of the transparent conductive layer may be a metal compound such as copper iodide. The material of the transparent conductive layer is preferably indium oxide (ITO) containing tin oxide, tin oxide containing antimony, and the like, and ITO is particularly preferable. When the material of the transparent conductive layer is ITO, it is preferable that the transparent conductive layer contains 80 to 99% by weight of indium oxide and 1 to 20% by weight of tin oxide.
[0177] The electrodes constituting the touch sensing electrode unit 35 (the touch sensor electrodes 36, the touch drive electrodes 37, or an electrode formed by integrating these) can be formed as a transparent electrode pattern between the first transparent substrate 31 and the second transparent substrate 33 by a conventional method. This transparent electrode pattern is electrically connected to, for example, a wiring line formed at the end of the transparent substrate. The wiring line is connected to, for example, a controller IC. The transparent electrode pattern can be in any shape depending on the application, such as a comb shape, a stripe shape, or a diamond shape. The transparent electrode pattern has a thickness of, for example, 10 nm to 100 nm. The transparent electrode pattern has a width of, for example, 0.1 mm to 5 mm.
[0178] [Embodiment of image display device] The image display device of this embodiment includes, for example, an image display panel 11A and an illumination system. Note that, instead of the image display panel 11A, the image display panels 11B and 11C shown in Figs. 4 and 5 can also be used. In the image display device, the image display panel 11A is disposed, for example, on the viewing side of the illumination system. The illumination system includes, for example, a backlight or a reflector, and irradiates light onto the image display panel 11A.
[0179] The image display device may be an organic EL display or a liquid crystal display. However, the image display device is not limited to this example. The image display device may be an electroluminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), or the like. The image display device can be used for home appliances, in-vehicle applications, public information displays (PID), and the like, and is preferably an in-vehicle display. EXAMPLES
[0180] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the examples shown below.
[0181] <Weight average molecular weight of (meth)acrylic polymer> The weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by gel permeation chromatography (GPC). The Mw / Mn of the (meth)acrylic polymer was also measured in the same manner. Analytical equipment: Tosoh HLC-8120GPC Column: Tosoh G7000H XL +GMH XL +GMH XL Column size: 7.8mmφ×30cm each, total 90cm Column temperature: 40℃ ·Flow rate: 0.8mL / min ·Injection volume: 100μL Eluent: Tetrahydrofuran Detector: Differential refractometer (RI) Standard sample: polystyrene
[0182] [Preparation of (meth)acrylic polymer A1] A monomer mixture containing 78.95 parts by weight of n-butyl acrylate (BA), 16 parts by weight of phenoxyethyl acrylate (PEA), 0.05 parts by weight of 4-hydroxybutyl acrylate (HBA), and 5 parts by weight of acrylic acid (AA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile (AIBN; manufactured by Kishida Chemical Co., Ltd.) was charged as a polymerization initiator together with 100 parts by weight of ethyl acetate per 100 parts by weight of the monomer mixture. While gently stirring the mixture, nitrogen gas was introduced into the flask to replace the atmosphere with nitrogen. The liquid temperature in the flask was maintained at around 55°C, and the polymerization reaction was carried out for 8 hours, thereby preparing a solution of (meth)acrylic polymer A1 with a weight average molecular weight (Mw) of 2.5 million. The glass transition temperature of (meth)acrylic polymer A1 calculated from the FOX formula was -43.5°C.
[0183] [Preparation of (meth)acrylic polymer A2] A solution of (meth)acrylic polymer A2 having a weight average molecular weight (Mw) of 1.9 million was prepared in the same manner as for (meth)acrylic polymer A1, except that the monomer mixture charged in the flask was 60 parts by weight of 2-methoxyethyl acrylate (MEA), 39 parts by weight of BA, and 1 part by weight of HBA. The glass transition temperature of (meth)acrylic polymer A2 calculated from the FOX formula was −52.0° C.
[0184] [Preparation of (meth)acrylic polymer A3] A solution of (meth)acrylic polymer A3 having a weight average molecular weight (Mw) of 2,000,000 was prepared in the same manner as for (meth)acrylic polymer A1, except that the monomer mixture charged in the flask was 67 parts by weight of MEA, 22 parts by weight of BA, 10 parts by weight of PEA, and 1 part by weight of HBA. The glass transition temperature of (meth)acrylic polymer A3 calculated from the FOX formula was −45.0° C.
[0185] [Preparation of (meth)acrylic polymer A4] A solution of (meth)acrylic polymer A4 having a weight average molecular weight (Mw) of 1.8 million was prepared in the same manner as for (meth)acrylic polymer A1, except that the monomer mixture charged in the flask was 99 parts by weight of BA and 1 part by weight of HBA. The glass transition temperature of (meth)acrylic polymer A4 calculated from the FOX formula was −55.0° C.
[0186] The monomers and the amounts used in synthesizing each (meth)acrylic polymer are summarized in the following Table 1. In the table, the notation "-" means that the corresponding component is not included.
[0187] [Table 1]
[0188] Example 1 [TAC film with hard coat layer] First, a resin solution (manufactured by DIC Corporation, product name: Unidic 17-806, solid content concentration: 80%) in which an ultraviolet-curable resin monomer or oligomer containing urethane acrylate as a main component is dissolved in butyl acetate was prepared. 5 parts by weight of a photopolymerization initiator (manufactured by BASF, product name: IRGACURE907) and 0.1 parts by weight of a leveling agent (manufactured by DIC Corporation, product name: GRANDIC PC4100) were added to the resin solution relative to 100 parts by weight of the solid content of the resin solution. Next, cyclopentanone and propylene glycol monomethyl ether were added to the resin solution in a weight ratio of 45:55 so that the solid content concentration in the resin solution was adjusted to 36%. This produced a hard coat layer forming material. The obtained forming material was applied onto a transparent protective film containing triacetyl cellulose (TAC film manufactured by Konica Minolta, product name "KC4UY") having a thickness of 40 μm to form a coating film. At this time, the thickness of the coating was adjusted so that the thickness of the hard coat layer obtained by curing the forming material was adjusted to 7 μm. Next, the coating was dried at 90° C. for 1 minute, and further exposed to a high-pressure mercury lamp with an integrated light amount of 300 mJ / cm 2 2 The coating film was irradiated with ultraviolet light of 10000 ohms. This caused the coating film to harden, resulting in a TAC film with a hard coat layer (HC).
[0189] [Polarizing plate] First, a polyvinyl alcohol film having a thickness of 80 μm was dyed in a 0.3% iodine solution (temperature 30° C.) for 1 minute between a plurality of rolls having different speed ratios, and stretched to a stretching ratio of 3 times. Next, the obtained stretched film was stretched to a total stretching ratio of 6 times while being immersed in an aqueous solution (temperature 60° C.) having a boric acid concentration of 4% and a potassium iodide concentration of 10% for 0.5 minutes. Next, the stretched film was washed by immersing it in an aqueous solution (temperature 30° C.) containing a potassium iodide concentration of 1.5% for 10 seconds. Next, the stretched film was dried at 50° C. for 4 minutes to obtain a polarizer having a thickness of 30 μm. A transparent protective film (thickness 30 μm) made of a modified acrylic polymer having a lactone ring structure was bonded to one main surface of the obtained polarizer via a polyvinyl alcohol adhesive. The above-mentioned TAC film (thickness 47 μm) with hard coat layer was bonded to the other main surface of the polarizer via a polyvinyl alcohol-based adhesive. At this time, the other main surface of the polarizer was bonded to a transparent protective film. The polarizer and the transparent protective film were bonded using a roll laminator. After bonding the polarizer and the transparent protective film, the obtained laminate was heated and dried at 70° C. for 5 minutes using an oven to obtain a polarizing plate consisting of a hard coat layer and a polarizing film.
[0190] [Anti-static layer] First, a coating solution with a solid content concentration of 0.5% by weight was prepared by mixing 50 parts of a solution containing PEDOT / PSS (manufactured by Nagase ChemteX Corporation, product numbers: N006-45-2A, N006-45-2B) and 50 parts of water. Next, the coating solution was applied to the surface of the polarizing plate on the polarizing film side. The obtained coating film was dried at 80°C for 2 minutes to prepare an antistatic layer. This resulted in a laminate L1 consisting of a polarizing plate and an antistatic layer. The thickness of the stop layer was 60 nm.
[0191] [Adhesive sheet] A solution of the (meth)acrylic pressure-sensitive adhesive composition of Example 1 was prepared by further blending 0.3 parts by weight of a crosslinking agent (manufactured by Tosoh Corporation, product name: Coronate 2770), 20 parts by weight of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Elexel AS110) as an antistatic agent, 0.5 parts by weight of an antioxidant (manufactured by BASF, product name: Irganox1010), and 0.4 parts by weight of a silane coupling agent (manufactured by Kaneka Corporation, product name: Silyl SAT010) relative to 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer A1.
[0192] Next, the obtained solution was applied to one side of a release liner (Mitsubishi Chemical Polyester Film Corporation's MRF38). The release liner was a polyethylene terephthalate film treated with a silicone-based release agent. The obtained coating film was dried at 155°C for 1 minute to obtain a laminate L2 in which an adhesive sheet was formed on the surface of the release liner. The adhesive sheet had a thickness of 20 μm.
[0193] [Optical laminate] Next, the adhesive sheet of the laminate L2 obtained above was transferred onto the antistatic layer of the laminate L1 to produce a laminate L3 in which a polarizing plate, an antistatic layer, an adhesive sheet, and a release liner were laminated in this order. The release liner was peeled off from the laminate L3 to obtain the optical laminate of Example 1.
[0194] Example 2 An optical laminate of Example 2 was obtained in the same manner as Example 1, except that in producing the adhesive sheet, a solution of (meth)acrylic polymer A2 was used, and 6 parts by weight of EMI-FSI was used as an antistatic agent per 100 parts by weight of the solid content of the (meth)acrylic polymer A2 solution was used.
[0195] Example 3 An optical laminate according to Example 3 was obtained in the same manner as in Example 2, except that the coating solution of PEDOT / PSS was applied to the polarizing film so that the antistatic layer had a thickness of 130 nm.
[0196] Example 4 An optical laminate according to Example 4 was obtained in the same manner as in Example 1, except that an adhesive sheet and an antistatic layer were prepared by the following method. First, a solution of (meth)acrylic polymer A3 was used in preparing an adhesive sheet. 8 parts by weight of EMI-FSI was used as an antistatic agent for 100 parts by weight of the solid content of the solution of (meth)acrylic polymer A3. A coating solution of PEDOT / PSS was applied to a polarizing film so that the thickness of the antistatic layer was 30 nm.
[0197] Example 5 An optical laminate according to Example 5 was obtained in the same manner as in Example 4, except that the coating solution of PEDOT / PSS was applied to the polarizing film so that the antistatic layer had a thickness of 60 nm.
[0198] Example 6 An optical laminate according to Example 6 was prepared in the same manner as in Example 4, except that the PEDOT / PSS coating solution was applied to the polarizing film so that the antistatic layer had a thickness of 130 nm. Got it.
[0199] Example 7 An optical laminate according to Example 7 was obtained by the same method as in Example 4, except that a laminate L1 consisting of a polarizing plate and an antistatic layer was prepared by the following method. First, a coating solution having a solid content concentration of 0.5% by weight was prepared by mixing 14 parts by weight of a solution containing CNT and a urethane binder (manufactured by Nagase Chemtex Corporation, product name: C-100A) and 86 parts by weight of water. Next, the coating solution was applied to the main surface of the polarizing plate on the polarizing film side. The obtained coating film was dried at 90°C for 1 minute to prepare an antistatic layer. As a result, a laminate L1 consisting of a polarizing plate and an antistatic layer was obtained. The thickness of the antistatic layer was 55 nm.
[0200] Example 8 An optical laminate of Example 8 was obtained in the same manner as Example 7, except that a coating liquid with a solids concentration of 0.5% by weight was applied to the main surface of the polarizing film side of the above-mentioned polarizing plate by mixing 15.1 parts by weight of a solution containing CNTs and a urethane-based binder (manufactured by Nagase ChemteX Corporation, product name: C-100A), 0.7 parts by weight of a binder containing an oxazoline group (manufactured by Nippon Shokubai Co., Ltd., product name: Epocross (registered trademark) WS-700), and 84 parts by weight of water.
[0201] Example 10 In producing the adhesive sheet, 15 parts by weight of EMI-FSI was used as an antistatic agent per 100 parts by weight of the solid content of the (meth)acrylic polymer A2 solution, and the PEDOT / PSS coating solution was applied to the polarized film so that the antistatic layer had a thickness of 30 nm. An optical laminate of Example 10 was obtained in the same manner as Example 2, except that:
[0202] Comparative Example 1 An optical laminate according to Comparative Example 1 was obtained in the same manner as in Example 1, except that an adhesive sheet was prepared by the following method and an antistatic layer was not prepared. In preparing the adhesive sheet, a solution of (meth)acrylic polymer A4 was used. 10 parts by weight of EMI-FSI was used as an antistatic agent for 100 parts by weight of the solid content of the solution of (meth)acrylic polymer A4.
[0203] The following evaluations were carried out for Examples 1 to 10 and Comparative Example 1. The evaluation results are shown in Table 2.
[0204] <Measurement of surface resistivity of adhesive sheet> In each of the Examples and Comparative Examples, the surface resistivity of the adhesive sheet at 25° C. was measured using a laminate L2 in which an adhesive sheet was formed on the surface of a release liner. The surface resistivity of the adhesive sheet in the laminate L2 was measured using a resistivity meter (Hiresta MCP-HT800 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) under conditions of an applied voltage of 250 V and an application time of 10 seconds.
[0205] <Measurement of surface resistivity of antistatic layer> In each of the Examples and Comparative Examples, the surface resistivity of the antistatic layer was measured using a laminate L1 consisting of a polarizing plate and an antistatic layer. The surface resistivity of the antistatic layer at 25° C. was measured using the resistivity meter described above in accordance with the method specified in JIS K6911:1995 under the conditions of an applied voltage of 10 V and an application time of 10 seconds.
[0206] <Measurement of surface resistivity of adhesive sheet side of optical laminate> The surface resistivity of the adhesive sheet side of the optical laminate according to each of the Examples and Comparative Examples was measured. The surface resistivity R1 of the adhesive sheet side of the optical laminate at room temperature (25°C) was measured according to the above method. The test was performed using a resistivity meter under conditions of an applied voltage of 250 V and an application time of 10 seconds.
[0207] The surface resistivity R of the adhesive sheet side of the optical laminate at -15°C was measured before and after the weather resistance test as follows. The polarizing plate side (hard coat layer side) of the laminate L3 was placed on a cold plate set at -15°C. After about 30 seconds, the release liner was immediately peeled off from the laminate L3 to measure the surface resistivity of the adhesive sheet side. The surface resistivity R of the adhesive sheet side of the optical laminate at -15°C was measured using the resistivity meter described above under the conditions of an applied voltage of 250V and an application time of 10 seconds. The weather resistance test was performed using an ultraviolet fading tester (manufactured by Suga Test Instruments, U48HB) by the above-mentioned method.
[0208] <Durability> The durability of the optical laminate was evaluated by the following method. The prepared optical laminate was fixed to the surface of a glass plate (Corning, Eagle XG) via the adhesive sheet to obtain an optical laminate with a glass plate. The fixing was performed in an atmosphere of 24°C and 50% RH. Next, the optical laminate with the glass plate was treated in an autoclave at 50°C and 5 atm (absolute pressure) for 15 minutes, and then left until it cooled to 24°C, so that the bonding of the optical laminate to the glass plate was stabilized. Next, the optical laminate with the glass plate was left standing in a heated atmosphere of 105°C for 500 hours. After leaving it standing, the atmosphere was returned to 24°C and 50% RH, and the peeling of the polarizing plate from the glass plate and the occurrence of bubbles between the glass plate and the polarizing plate were visually confirmed, and the durability was evaluated as follows. (Evaluation Criteria) A: No visible changes such as foaming or peeling were observed. B: Separate peeling or slight bubbling is observed at the edge, but is within the range that does not cause any practical problems. C: Slight continuous peeling or bubbling is observed at the edge, but is within the range that does not cause any practical problems. D: Significant peeling or foaming is observed at the edge, and it is problematic for practical use.
[0209] <Evaluation of white spots> The white spots of the optical laminate were evaluated by the following method before and after the weather resistance test. A glass plate simulating a front transparent member was attached to the optical film side of the prepared optical laminate via OCA (manufactured by Nitto Denko Corporation, LUCIACS CS9821; acrylic acid monomer-free adhesive, thickness 200 μm) to prepare an evaluation laminate simulating an image display device. Next, the evaluation laminate was attached to the viewing side of an in-cell type liquid crystal cell via the adhesive sheet to prepare an in-cell type liquid crystal cell with a laminate. Next, a polarizing plate was attached to the opposite side of the viewing side of the in-cell type liquid crystal cell with the laminate so as to be in a cross-Nicol relationship to prepare a liquid crystal display panel. This liquid crystal display panel was cooled with a cold plate set to -15 ° C., and then immediately set on a backlight device, and static electricity was generated by rubbing the polarizing plate surface on the viewing side several times with nitrile gloves. The time until the white spots generated by static electricity disappeared was measured and evaluated according to the following criteria. The weather resistance test was carried out using an ultraviolet fading tester (U48HB, manufactured by Suga Test Instruments Co., Ltd.) according to the above-mentioned method. Note that the evaluation result that is problematic for practical use is "D". (Evaluation Criteria) A: No blank spots occur. B: White spots appear when rubbed several times, but disappear within 1 second. C: White spots appear when rubbed several times, but disappear within 1 second and less than 5 seconds. D: White spots appear after just one rub, and it takes 5 seconds or more for them to disappear.
[0210] [Table 2]
[0211] As shown in Table 2, in the examples, the surface resistivity of the pressure-sensitive adhesive sheet side of the optical laminate at −15° C. was 1.0×10 10 The optical laminate according to the embodiment is more suitable for suppressing display defects, typically white spots due to charging, in a low-temperature environment. [Industrial Applicability]
[0212] The optical laminate of the present invention can be particularly suitably used in image display devices used in environments such as the inside of a vehicle where other electronic devices are present nearby and static electricity is likely to be generated, and where the temperature is likely to drop to low temperatures due to the influence of the outside air temperature. [Explanation of symbols]
[0213] 1 Adhesive sheet 2 Antistatic layer 3. Optical Film 4 Release Liner 10A, 10B Optical laminate 11A, 11B, 11C Image display panel 30A, 30B Image display cell 31 First transparent substrate 32 Image forming layer 33 Second transparent substrate 35 Touch sensing electrode 36 Touch sensor electrode 37 Touch drive electrode 40 Conductive Layer
Claims
1. An optical laminate comprising an adhesive sheet, an antistatic layer, and an optical film, the pressure-sensitive adhesive sheet is formed from a pressure-sensitive adhesive composition containing a polymer (A) and an antistatic agent, The surface resistivity of the pressure-sensitive adhesive sheet side of the optical laminate at −15° C. is 1.0×10 10 An optical laminate having a resistivity of Ω / □ or less.
2. The surface resistivity of the antistatic layer at 25° C. is 3.0×10 8 The optical laminate according to claim 1, having a resistance to vibration of Ω / □ or less.
3. The surface resistivity of the antistatic layer at 25° C. is 1.0×10 7 Ω / □ or more 1.0×10 8 The optical laminate according to claim 2, having a resistance of less than Ω / □.
4. The optical laminate according to claim 1 , wherein the polymer (A) is a (meth)acrylic polymer.
5. The optical laminate according to claim 1 , wherein the polymer (A) has a polyether structure.
6. The optical laminate according to claim 1 , wherein the polymer (A) has a structural unit derived from a monomer represented by the following formula (1): 【Chemistry 1】 In the formula (1), R 1 is a hydrogen atom or a methyl group, R 2 is an alkyl group which may be linear or branched, and n is an integer of 1 to 15.
7. The optical laminate according to claim 5 , wherein the polymer (A) has a structural unit derived from an aromatic ring-containing monomer.
8. The optical laminate according to claim 1 , wherein in the pressure-sensitive adhesive composition, the blending amount of the antistatic agent is less than 10 parts by weight per 100 parts by weight of the polymer (A).
9. 2. The optical laminate according to claim 1, wherein the glass transition temperature of the polymer (A) calculated from the FOX formula is −40° C. or lower.
10. The optical laminate according to claim 9, wherein the glass transition temperature is −45° C. or lower.
11. An image display panel comprising the optical laminate according to any one of claims 1 to 10.
12. An image display device comprising the image display panel according to claim 11.
Citation Information
Patent Citations
Optical film with adhesive layer and liquid crystal panel
JP2021096308A
Polarizer and image display device
JP2022074622A
Polarizing plate and picture display unit using the same
JP2022129959A
Metal connecting apparatus of lead tab of secondary battery
KR102472380B1
Conductive polymer layer as an antistatic protective shield for polarizing filters
JP2015509615A